Goal Programming Method in Optimizing Course Student Admission, Operational Costs and Profits - Muhammad Khahfi Zuhanda; Saib Suwilo; Opim Salim Sitompul; Mardingsih Mardingsih (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
In today's business competition, educational institutions or courses require optimizing profits. However, this is not easy because, in its implementation, there are many priority objective functions that must be fulfilled. In this case, the course institution has different class programs, namely literacy, numeracy, and math olympiad programs, with various operational costs per program type and course fees per program type. This problem requires setting priorities because of the limited number of revenues, operating costs, and profit targets. In this paper, the researcher uses Winter's Exponential Smoothing forecasting model to determine the number of students, operating costs, and profits in the following year. Then the researcher analyzes the planning with the goal programming method to minimize the deviation of the multi-objective programming. This research shows that the number of student admissions who can meet market demand for January 2021 decreased by 5.41%, in February decreased by 3.20%, in March decreased by 1.29%, April remained constant, in May increased by 1.44%, June increased by 2.16%, July increased 2.82%, August increased 2.78%, September increased 3.47%, October increased 3.22%, November an increase of 3.33%, and for December an increase of 2.69%. The total operational cost that does not exceed the target limit is Rp. 30,475,0000 for one year. The total profit has reached the target to be achieved, which is Rp. 322,150,000 for one year.